Chlamydia trachomatis and Human Papillomavirus Infection in Women From Southern Hunan Province in China: A Large Observational Study - Chen, Hongliang; Luo, Lipei; Wen, Yating; He, Bei; Ling, Hua; Shui, Jinwei; He, Ping; Hou, Xiaoli; Tang, Shixing; Li, Zhongyu (Frontiers in Microbiology, 2020)
Chlamydia trachomatis and human papillomavirus (HPV) are the most common pathogens of sexually transmitted infections (STIs), which can increase the risk of cervical cancer and infertility. The purpose of this study was to evaluate the prevalence, genotype and risk factors of C. trachomatis and/or HPV infection in women attending the annual physical examination, assistant reproductive treatment and visiting the gynecology clinics from Southern Hunan province in China. Cervical-swab samples were collected from 5006 participants. We found that the overall prevalence of C. trachomatis, HPV infection and C. trachomatis/HPV coinfection was 4.7% (236/5006), 15.5% (778/5006) and 1.2% (59/5006), while the prevalence of asymptomatic infection of that was 3.8% (38/1006), 10.8% (109/1006) and 0.6% (6/1006) respectively. Furthermore, 25.0% (59/236) of C. trachomatis infection and 7.6% (59/778) of HPV infection were attributable to C. trachomatis and HPV coinfection. C. trachomatis and HPV infection were more often observed in young women of less than 25 years (10.4% and 21.3%, respectively) and in the outpatients from gynecology clinics (5.2% and 18.0%, respectively). Of note, a higher prevalence of C. trachomatis infection was observed in HPV-positive women (7.6%) than HPV- negative ones (4.2%), and vice versa. The top three C. trachomatis genotypes were E (1.4%), F (1.1%) and J (0.8%), and the counterparts of HPV genotypes were HPV52 (4.2%), HPV16 (2.3%) and HPV58 (2.2%) respectively. Among the 151 outpatients with colposcopy data, HPV infection was associated with severe cervical lesions with OR of 15.86 (95% CI 3.14-80.0, P< 0.001) while C. trachomatis infection was more likely associated with a low grade colposcopy impression (OR=3.25, 95% CI: 1.22-8.65, P= 0.018). Our data highlight the high prevalence of asymptomatic C. trachomatis and HPV infection, particularly among women of < 25 years. The two pathogens may serve as mutual risk factors to increase the risk of infections and cervical lesions. Widespread implementation of HPV and C. trachomatis screening programs, especially for young women, would be an effective strategy to relieve the burden of sexually transmitted infections.